Gambaran Pengetahuan dan Perilaku Masyarakat Desa Gambus Laut Terhadap Pencegahan Demam Berdarah Dengue - Zahra Nasution, Maharani; Khairina Ashar, Yulia; Pramita Gurning, Fitriani; Hasanah, Uswatul; Barokah, Wuni (JUKEJ : Jurnal Kesehatan Jompa, 2025)
Dengue Hemorrhagic Fever (DHF) is a viral infectious disease that has become a global health problem with a significant increase in cases, especially in Indonesia. In 2024, there were more than 14.6 million cases of DHF worldwide, with around 12,000 deaths. In Indonesia alone, throughout 2025, there were around 80,000 cases and hundreds of deaths, especially in coastal areas such as Gambus Laut Village, Batu Bara Regency, which has a high risk due to suboptimal environmental and hygiene conditions. Although the level of public knowledge about DBD is relatively good, it is not always followed by effective preventive behavior, so cases still occur. Therefore, appropriate education and intervention are crucial to improve knowledge and encourage preventive behavioral changes. This study used a cross-sectional design with purposive sampling of 30 respondents to describe public knowledge and behavior related to dengue prevention and measure the effectiveness of education through pretest-posttest questionnaires. The results showed a significant increase in knowledge after education, with the average score rising from 14.5 to 16.5 and a p-value of 0.001. These findings indicate that socialization and poster media are effective in increasing knowledge and are expected to encourage better preventive behavior to reduce the number of DHF cases in the community.